Migrant Hearts and the Atlantic Return : Transnationalism and the Roman Catholic Church - Napolitano, Valentina (Book collections on Project MUSE., 2015)
Through the rendering of Catholic Church migration's debates this book shows how Latin American lay and religious migration in Rome is an Atlantic Return from the Americas challenging an Euro-centric Catholic identity and how multiple forms of being Catholic inform gender, labour and sexuality at the heart of Catholicism in Europe.